Efetividade da clorexidina na prevenção de pneumonia Nosocomial em unidades de terapia intensiva: overview - Flavia Rabello (2016)
hospital institutions from different countries use chlorhexidine in the oral hygiene of patients in intensive care units. No! However, the effectiveness of this pharmacological agent in the prevention of nosocomial pneumonia and controversial for all populations of patients hospitalized in these units. The aim of this study was to summarize the evidence on the effectiveness of the use of chlorhexidine in care! oral hygiene! of patients! intensive care units, in the prevention of nosocomial pneumonia. The study was conducted by means of a overview of systematic reviews using items found on the basis of PubMed data, -Cochrane- Library, -! LILACS, -CRD- e-CINHAL and manual search and gray literature. included were 16 systematic reviews (14 with! meta-analysis), most of them with high quality methodological. The results showed that in the intensive care unit with adult population of cardiac surgery, Chlorhexidine was effective in the prevention of nosocomial pneumonia. However, the effectiveness of chlorhexidine was controversial in intensive care units with populations in varied conditions clinicoDcirurgicas, requiring ventilation Mechanical for more than 48 hours. While chlorhexidine has shown better statistical results of efficacy compared to control and minimal adverse comefeitos. In critical clinical pictures, chlorhexidine may be insufficient to promote a Restraining oral decontamination pathogens, which outweighs the risk infection of an endotracheal tube, which acts as a reservoir of continuous driving of microorganisms for the lungs. In this context, this study contributes to! Evaluation of! Current therapeutic approach to hospitalized patients in intensive care units, in view of the evidence of the use of chlorhexidine in prevention of nosocomial pneumonia.